Hubungan antara Kadar D-Dimer Hari Pertama Masuk Rumah Sakit dan Hari Ketujuh dengan Tampilan Klinis pada Pasien Stroke Iskemik Akut - Ayu Nurul Zakiah (Fakultas Kedokteran USU, 2018)
AbstrakPendahuluan: Stroke merupakan ancaman terbesar menimbulkan kecacatan pada manusia. Diagnosisstroke iskemik berdasarkan pemeriksaan klinisi, pencitraan otak dan laboratorium (d-dimer). Menurutbeberapa penelitian, d-dimer meningkat dengan meningkatnya keparahan stroke, terutama pada stroketromboembolik.Metode: Penelitian kohort prospektif dari bulan Agustus - September 2016 terhadap 30 pasien strokeiskemik akut dan dilakukan anamnesis, Computed Tomography (CT) scan kepala, pengukuran tinggibadan, berat badan, indeks massa tubuh, Hemorrhagic Screening Test (HST), d-dimer hari pertama danhari ketujuh serta skor Indeks Barthel hari pertama dan hari ketujuh.Hasil: Dari 30 subyek, terdapat perbedaan bermakna rerata kadar d-dimer hari pertama dan hari ketujuh(p<0.05). Terdapat perbedaan bermakna skor Indeks Barthel hari pertama dan hari ketujuh (p<0.05).Terdapat korelasi negatif yang rendah kadar d-dimer hari pertama dengan skor Indeks Barthel haripertama (r=-0.383; p<0.05). Terdapat korelasi negatif sedang kadar d-dimer hari ketujuh dengan skorIndeks Barthel hari ketujuh (r=-0.576;p<0.05).Kesimpulan: Terdapat korelasi negatif antara kadar d-dimer dengan skor Indeks Barthel pada pasienstroke iskemik akutKata kunci: d-dimer, tampilan klinis, Indeks Barthel, stroke iskemikAbstractIntroduction: Stroke, one of the biggest threats is the cause of disability in people's lives. The diagnosisof ischemic stroke based on examination of clinicians, plus the brain imaging and laboratoryexaminations (d-dimer). According to some research, the d-dimer levels increased with increasingseverity of stroke, especially on stroke thromboembolic.Methods: A prospective cohort study from August - September 2016 against 30 acute ischemic strokepatients and anamnesis, a head Computed Tomography (CT) scan, the measurement of height, weight,body mass index, Hemorrhagic Screening Test (HST), d-dimer first day and the seventh day and the firstand the seventh day of the Barthel Index score.Results: Of the 30 subjects, there is a meaningful difference in average d-dimer’s value on the first dayof hospital admission and the seventh day (p<0.05). There are meaningful differences Barthel indexscore on the first day of hospital admission and the seventh day (p<0.05). There is a negative lowcorrelation d-dimer’s value on the first day with the Barthel Index score on the first day (r=-0.383;p<0.05).There are negative medium correlations of d-dimer’s value of the seventh day with the Barthel Indexscore on the seventh day (r=-0.576; p<0.05).Conclusion: There’s a negative correlation between d-dimer’s value with Barthel Index score in strokeischemic patientsKeywords: d-dimer, clinical outcome, Barthel Index, ischemic stroke